The Art of War - Sunzi, 6th cent. B.C. (Penguin Books, 2009)
For more than two thousand years, Sun-tzu's "The Art of War" has provided leaders with essential advice on battlefield tactics, managing troops and terrain, and employing cunning and deception. An elemental part of Chinese culture, it has also become a touchstone for the Western struggle for survival and success.